Self Improvement Through Public Speaking laws of leadership - Marden, Orison Sweet (Mechanicsburg Executive Books, 2007)
Research has confirmed again and again that public speaking is essential to success. This practical guide by Orison Swett Marden will help you to understand the significance of gaining the verbal advatage needed for your career, personal and social life.
Read by Charlie Jones
Keywords: Public Speaking